Territory in the Constitutional Standards of Unitary States - Markhgeym, Marina V.; Nifanov, Aleksej N.; Novikova, Alevtina E.; Poluhin, Oleg N.; Tonkov, Evgeniy E. (Journal of History Culture and Art Research, 2017)
The article is based on the analysis of the constitutions of seven European countries (Albania, Hungary, Greece, Spain, Malta, Poland, Sweden). The research allows to reveal general and specific approaches to consolidation of norms on territories in a state and give the characteristic of the corresponding constitutional norms. Given the authors ' comprehensive approach to the definition of the territory of the state declared constitutional norms were assessed from the perspective of the fundamental principles and constituent elements of the territory. Considering the specifics of the constitutional types of state territories authors suggest typical and variative models and determine the constitutions of unitary states, distinguished by their originality in the declared group of legal relations. The original constitutional language areas associated with the introduction at the state level, these types of areas that are not typical for other countries.